Intrinsic motivations for productive ageing - Norisan Abd Karim; Haryani Haron; Natrah Abdullah; Wan Adilah Wan Adnan; Sharifah Muzlia Syed Mustafa (Institute of Advanced Engineering and Science, 2019)
The involvement of the elderly in the activities is low compare to younger adult due to their frailty. This paper presents intrinsic motivations for productive ageing where it highlights the factors that motivate the elderly to participate in the activities. There are thirteen elderly respondents came from the people in the urban Klang Valley. The qualitative data analysis approach is used in this study. There are five intrinsic factors, which, consist of Autonomy, Competence, Relatedness, Curiosity and Altruism that motivate the participation of the elderly in volunteering, caregiving and self-development activities in this study. This research focuses on activities that resulted intrinsic values and not on monetary value like most of past researchers. Intrinsic motivation features are significant features in ICT as the identification of the ICT features is based on motivation to use the ICT.